The Effectiveness of the Combination of Virgin Coconut Oil (VCO) and Lemongrass (Cymbopogon nardus L) on Skin Moisture in Patients Undergoing Hemodialysis - Sunarti Sunarti; Karmila Br Kaban; Elis Anggeria (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Chronic kidney disease (CKD) is a chronic disease caused by a progressive, irreversible and chronic decline in kidney function, causing the accumulation of toxins such as urea, phosphate, and creatinine in the blood because the kidneys cannot filter them properly, causing mineral imbalances and disorders of the sweat and oil glands, which cause the skin to become dry, scaly and trigger itching. This study aims to analyze the combination of VCO and Lemongrass for skin care in patients undergoing hemodialysis therapy. This research method is quantitative using a quasi-experimental design with a one group pre-test-post-test design between the intervention group and the control group. The sampling technique used purposive sampling on 20 respondents in the intervention group and 20 respondents in the control group. The results of the Wilcoxon test showed an increase in skin moisture in the intervention group with a p value = 0.002 and the control group with a p value = 0.046 (P <0.005). The results of the visual skin dryness test and uremic pruritus did not show significant results, so it is hoped that patients can use the combination of VCO and lemongrass as an alternative for skin care for CKD patients undergoing hemodialysis.